<em>A) 22cm</em>
<em>(</em><em> </em><em>divide the length value by 100</em><em>)</em>
<em>2</em><em>2</em><em>/</em><em>1</em><em>0</em><em>0</em><em> </em><em>which</em><em> </em><em>gives</em><em> </em><em>you</em><em>:</em>
<em><u>=</u></em><em><u>0.22m</u></em>
<em>B</em><em>)</em><em> </em><em>180km</em>
<em>(</em><em> </em><em>multiply the length value by </em><em>1000</em><em>)</em>
<em>1</em><em>8</em><em>0</em><em>×</em><em>+</em><em>1</em><em>0</em><em>0</em><em> </em><em>which</em><em> </em><em>gives</em><em> </em><em>you</em><em>:</em>
<em><u>=</u></em><em><u>180000m</u></em>
<em>C</em><em>)</em><em> </em><em>300mm</em>
<em>(</em><em> </em><em>divide the length value by 1000</em><em>)</em>
<em>3</em><em>0</em><em>0</em><em>/</em><em>1</em><em>0</em><em>0</em><em>0</em><em> </em><em>which</em><em> </em><em>gives</em><em> </em><em>you</em><em>:</em>
<em><u>=</u></em><em><u>0.3m</u></em>
<em> </em>
Answer:
y = -2x + 9
Step-by-step explanation:
y = -2x + 7
(4, 1)
1 = -2 ( 4 ) + b
1 = -8 + b
b = 9
y = -2x + 9
Answer:
31/30
Step-by-step explanation:
-3 3/10+4 1/3
-3 9/30+4 10/30
31/30